2008
DOI: 10.1002/lt.21623
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl starch-based preservation solutions enhance gene therapy vector delivery under hypothermic conditions

Abstract: Isolated liver perfusion offers a unique prospect for safe, effective targeting of gene therapies that can be directed against allograft rejection or recurrent diseases such as reinfection by hepatitis C virus (HCV). We aimed to examine the effect of organ preservation solutions on vector-based gene therapy delivery under hypothermic conditions. University of Wisconsin (UW) solution, histidine tryptophan ketoglutarate (HTK), EloHaes, sodium-poly(ethylene glycol)-UW solution [Institut Georges Lopez 1 solution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We used a subgenomic HCV replication model based on a Huh7 hepatoma cell line containing the non-structural sequence of the HCV genome with a luciferase reporter gene (Huh7-ET), mimicking viral replication without virus particle production 24. As reported previously, LV-shNS5b resulted in a mean±SD maximum inhibition of HCV replication of 98±0.5% (n=8, p<0.001) at the highest transduction efficiency 8 25. However, at suboptimal transduction efficiency, the percentage inhibition of viral replication as measured by luciferase activity significantly exceeded the percentage of transduced cells as measured by GFP expression (figure S1 in online supplement).…”
Section: Resultsmentioning
confidence: 93%
“…We used a subgenomic HCV replication model based on a Huh7 hepatoma cell line containing the non-structural sequence of the HCV genome with a luciferase reporter gene (Huh7-ET), mimicking viral replication without virus particle production 24. As reported previously, LV-shNS5b resulted in a mean±SD maximum inhibition of HCV replication of 98±0.5% (n=8, p<0.001) at the highest transduction efficiency 8 25. However, at suboptimal transduction efficiency, the percentage inhibition of viral replication as measured by luciferase activity significantly exceeded the percentage of transduced cells as measured by GFP expression (figure S1 in online supplement).…”
Section: Resultsmentioning
confidence: 93%
“…ing cold preservation [127] and in protocols for ex vivo modification. In the recipient, the therapeutic gene will be expressed after transplantation [128].…”
Section: Pharmacological Manoeuvresmentioning
confidence: 99%
“…Hydroxyethyl starch (HES), a component of UW Belzer, could account for the boosted HCV entry. In fact, it was shown that the entry of VSV pseudotyped lentiviral particles was facilitated in the presence of UW Belzer suggesting its use in gene therapy during cold storage of liver transplants . Even though HES is a non‐ionic compound, it appears to neutralize repulsive forces between pseudoparticles and the cell surface.…”
Section: Discussionmentioning
confidence: 99%